2016
DOI: 10.3389/fnins.2016.00152
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Transient Target Stimuli in a Steady-State Somatosensory Evoked Potential-Based Brain–Computer Interface Setup

Abstract: In earlier literature, so-called twitches were used to support a user in a steady-state somatosensory evoked potential (SSSEP) based brain–computer interface (BCI) to focus attention on the requested targets. Within this work, we investigate the impact of these transient target stimuli on SSSEPs in a real-life BCI setup. A hybrid BCI was designed which combines SSSEPs and P300 potentials evoked by twitches randomly embedded into the streams of tactile stimuli. The EEG of fourteen healthy subjects was recorded,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
28
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(29 citation statements)
references
References 30 publications
(63 reference statements)
1
28
0
Order By: Relevance
“…In our experimental results (Fig. 6), the proposed method showed higher performances (56.4%, and 57.9%) compared to the previous study as 48.6% [29]. Despite considering the differences in stimuli inducing SSSEP and in the number of subjects from the previous study and the current study, our approach is valuable.…”
Section: Figurementioning
confidence: 58%
See 4 more Smart Citations
“…In our experimental results (Fig. 6), the proposed method showed higher performances (56.4%, and 57.9%) compared to the previous study as 48.6% [29]. Despite considering the differences in stimuli inducing SSSEP and in the number of subjects from the previous study and the current study, our approach is valuable.…”
Section: Figurementioning
confidence: 58%
“…Our study showed that the proposed method can help to improve the classification accuracy of the selective attention and inattention and show spatially clear and distinguishable patterns for vibration stimuli-induced SSSEP-based BCIs. In the previous twitch-based multiclass SSSEP study, Pokorny et al [29], the cross-validation accuracy for multi-class (concentrating on left-hand, right-hand, and idle class) were averaged 48.6% within 14 subjects using C-2 tactor (Engineering Acoustics, Inc., Casselberry, Florida, USA) with finger clip to induce SSSEP [29]. Unlike our experimental setup, the EEG signals from 29 channels focused on the somatosensory cortex and the EOG signals from 3 channels were recorded [29].…”
Section: Figurementioning
confidence: 99%
See 3 more Smart Citations